(untitled) (Международный научный журнал «Инженер», 2026)
This article presents an in-depth examination of the ecological and economic efficiency of green infrastructure components within the context of modern urban planning. It explores the environmental and social benefits of green spaces, vertical gardens, ecological transport systems, solar panels, and other energy-efficient technologies. Drawing on academic research, international case studies, and contemporary urban projects, the paper analyzes how these elements contribute to the sustainability and livability of urban environments. Particular attention is given to current initiatives in Uzbekistan, such as the nationwide “Yashil Makon” (Green Space) campaign and the “New Andijon” smart city development. The study identifies key challenges including regulatory barriers, limited technical capacity, and financial constraints. Based on these findings, the article proposes practical recommendations aimed at improving the implementation and effectiveness of green infrastructure. This research contributes to the development of sustainable, resilient cities and highlights the strategic role of environmental design in shaping healthier urban futures.